2022
DOI: 10.1007/s12525-022-00600-9
|View full text |Cite
|
Sign up to set email alerts
|

Applying XAI to an AI-based system for candidate management to mitigate bias and discrimination in hiring

Abstract: Assuming that potential biases of Artificial Intelligence (AI)-based systems can be identified and controlled for (e.g., by providing high quality training data), employing such systems to augment human resource (HR)-decision makers in candidate selection provides an opportunity to make selection processes more objective. However, as the final hiring decision is likely to remain with humans, prevalent human biases could still cause discrimination. This work investigates the impact of an AI-based system’s candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 98 publications
0
0
0
Order By: Relevance
“…Papers classified under categories C, D, and E demonstrated varying, yet more substantiated, levels of engagement with ethical theories and frameworks. A closer examination of the papers in each category reveals distinct patterns in the depth and quality of ethical engagement: Computer Science (Hofeditz et al, 2022), (Baum et al, 2022), (El-Nasr & Kleinman, 2020), (Nicodeme, 2020), (Gerdes, 2021), (Dexe et al, 2020), (Lindner & Möllney, 2019), (Falomir & Costa, 2021), (van Otterlo & Atzmueller, 2020) Ethics & Society (Fleisher, 2022), (Larsson & Heintz, 2020), (Narayanan & Tan, 2023), (Kasirzadeh & Smart, 2021) Medicine/Healthcare (Martinho et al, 2021), (Morris et al, 2023), (Jongepier & Keymolen, 2022), (Kempt et al, 2022), (Heinrichs & Eickhoff, 2020), (Herzog, 2022a) 2020) conducts an ethical assessment of explainability in AI-based clinical decision support using the "Principles of Biomedical Ethics," while (Sullivan & Verreault-Julien, 2022) proposes using the capability approach to provide ethical standards for algorithmic recourse. Notably, papers from philosophical, social science, and interdisciplinary backgrounds (e.g., (Amann et al, 2020)) often provide more extensive engagement with ethical theories and frameworks compared to papers from purely technical domains.…”
Section: Depth and Extent Of Ethical Discussionmentioning
confidence: 99%
“…Papers classified under categories C, D, and E demonstrated varying, yet more substantiated, levels of engagement with ethical theories and frameworks. A closer examination of the papers in each category reveals distinct patterns in the depth and quality of ethical engagement: Computer Science (Hofeditz et al, 2022), (Baum et al, 2022), (El-Nasr & Kleinman, 2020), (Nicodeme, 2020), (Gerdes, 2021), (Dexe et al, 2020), (Lindner & Möllney, 2019), (Falomir & Costa, 2021), (van Otterlo & Atzmueller, 2020) Ethics & Society (Fleisher, 2022), (Larsson & Heintz, 2020), (Narayanan & Tan, 2023), (Kasirzadeh & Smart, 2021) Medicine/Healthcare (Martinho et al, 2021), (Morris et al, 2023), (Jongepier & Keymolen, 2022), (Kempt et al, 2022), (Heinrichs & Eickhoff, 2020), (Herzog, 2022a) 2020) conducts an ethical assessment of explainability in AI-based clinical decision support using the "Principles of Biomedical Ethics," while (Sullivan & Verreault-Julien, 2022) proposes using the capability approach to provide ethical standards for algorithmic recourse. Notably, papers from philosophical, social science, and interdisciplinary backgrounds (e.g., (Amann et al, 2020)) often provide more extensive engagement with ethical theories and frameworks compared to papers from purely technical domains.…”
Section: Depth and Extent Of Ethical Discussionmentioning
confidence: 99%
“…XAI models for administrative tasks in areas other than healthcare have already begun to be explored such as: data management, record keeping, financial decision making, auditing, text classification and for hiring staff [67][68][69][70][71][72]. Indeed, further research in the areas of machine learning, Natural Language Processing (NLP), chatbots, and Robotic Process Automation (RPA) is warranted, particularly considering these AI approaches have been identified as valuable tools for handling administrative tasks within PC.…”
Section: Research Objective 3: Addressing the Specific Requirementsmentioning
confidence: 99%
“…The six significant theories that are deployed in algorithmic functioning are "ethical egoism-preference based, deontology-rule based, utilitarianism (principle-based), relativism, virtue ethics, and the ethics of care" (Rodgers et al, 2023). Hofeditz et al (2022) suggested that discrimination of AI may result from algorithms, but AI-based decision tools can make visible and retrievable errors; therefore, they can lead to more successful hires and reduced costs, eliminating unethical features and providing diversity in recruitment. The author deems that AI is unlikely to replace humans in recruiting procedures but rather to increase the role of humans to augment human decision-making for better outcomes.…”
Section: Ethics Of Ai In Hrmmentioning
confidence: 99%